A population history of Tokelau – genetic variation and change in atoll populations. (2nd January 2023) - Gosling, Anna L.; Lord, Edana; Boocock, James; Cameron-Christie, Sophia; Horsburgh, K. Ann; Kardailsky, Olga; Prost, Stefan; Wilcox, Stephen; Addison, David; Thompson, Adam; Kalolo, John; Clarke, Andrew C.; et al.
Abstract: Tokelau is a remote archipelago of atolls in western Polynesia, located approximately 500 km north of Samoa. It is thought to have been settled as part of the Austronesian expansion(s). However, its exact role in this population dispersal is not completely understood. Here we describe the results of complete mitochondrial genome sequencing for both the current inhabitants and ancient individuals from the archipelago in addition to an assessment of Y-chromosome diversity among the present population. We find relatively little genetic diversity compared with other western Polynesian populations, most likely due to historically reported bottleneck events. However, the presence of rare mitochondrial lineages hints at prehistoric occupation by peoples from the northwest (e.g., Tuvalu and Micronesia). Ancient DNA data from Atafu, the northernmost Tokelauan atoll, is further consistent with abandonment and later resettlement of the island from a Samoan or Samoan-derived source population. Moreover, the ancient and modern mitogenomes also suggest links with other atoll populations in the western Pacific.